Excellent graft and patient survival after renal transplantation from donors after brain death with acute kidney injury: a case-control study - Benck, Urs Tobias; Schnülle, Peter; Krüger, Bernd; Nowak, Kai; Riester, Thomas; Mundt, Heiko; Birck, Rainer; Krämer, Bernhard; Schmitt, Wilhelm (International urology and nephrology, 2015)
BackgroundWhether organs from donors after brain death (DBD) with acute kidney injury (AKI) should be accepted for transplantation is still a matter of debate.MethodsThis was a retrospective, center-based, matched cohort study of 33 renal transplant patients who received a renal allograft from a DBD with AKI. Sixty-five kidney transplants without donor AKI transplanted directly before and after the index transplantation served as controls.ResultsAll AKI donors were classified according to RIFLE criteria: 9.1 % Risk, 54.6 % Injury, and 36.4 % Failure. Mean serum creatinine was 2.41 ± 0.88 mg/dL at procurement and 1.06 ± 0.32 mg/dL on admission. AKI donors had lower 24-h urine production (3.22 ± 1.95 vs. 4.59 ± 2.53 L, p = 0.009) and received more frequently noradrenaline (93.9 vs. 72.3 %, p = 0.02) and/or adrenaline (15.2 vs. 1.5 %, p = 0.02). Recipient and transplant characteristics were similar except a more favorable HLA match in control patients (p = 0.01). Hemodialysis posttransplant was more frequently used in AKI recipients (14/33 [42.4 %] vs. 18/65 [27.7 %], p = 0.17). While significant elevations in serum creatinine were noted in these patients until 10 days after transplantation, this difference lost statistical significance by day 14. One-year graft survival was very similar when comparing the groups (93.6 % [95 % CI 76.8-98.4 %] vs. 90.3 % [95 % CI 79.6-95.5 %], log rank p = 0.58).ConclusionsKidneys from AKI donors can be transplanted with excellent intermediate prognosis and should not be discarded.
Gesehen am 31.08.2017